Mechanics and calculations of textile machinery - Gokarneshan, N. (Woodhead Publishing Ltd, 2012)
Mechanics and calculations of textile machinery deals with the mechanics and dynamics of textile machines. The first chapter examines various types of power drives used in textile machinery. The second chapter discusses types of gears. The third chapter deals with the design aspect of cone drums used in spinning machines. The different types and design of cams used in ring frames and looms are discussed in the following chapters. The final part of the book focuses on energy calculations in textile machines, frictional forces and their calculation, clutches and brakes.
Keywords: Textile machinery.; elektronické knihy; electronic books